2018
DOI: 10.1002/anie.201711839
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Nanoprecipitation toward Stable and Responsive Microbubbles and Their Use as a Resuscitative Fluid

Abstract: A new approach has been developed to prepare stable microbubbles (MBs) by interfacial nanoprecipitation of bioabsorbable polymers at air/liquid interfaces. This facile method offers robust control over the morphology and chemophysical properties of MBs by simple chemical modifications. This approach is amenable to large-scale manufacturing, and is useful to develop functional MBs for advanced biomedical applications. To demonstrate this, a MB-based intravenous oxygen carrier was created that undergoes pH-trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 35 publications
0
50
0
Order By: Relevance
“…infusion of LOMs requires careful titration of the delivered gas fraction to avoid depletion of the local oxygen sink conditions within the vasculature; failure to do so results in prolonged microbubble persistence leading to pulmonary emboli and increased incidences of cardiac arrest (Figure D) Our laboratory has also shown that i.v. delivery of LOMs in a swine model of CA causes in vivo formation of lethal large gas emboli . As mentioned above, this is likely because i.v.…”
Section: Lipid‐based Microbubblesmentioning
confidence: 99%
See 4 more Smart Citations
“…infusion of LOMs requires careful titration of the delivered gas fraction to avoid depletion of the local oxygen sink conditions within the vasculature; failure to do so results in prolonged microbubble persistence leading to pulmonary emboli and increased incidences of cardiac arrest (Figure D) Our laboratory has also shown that i.v. delivery of LOMs in a swine model of CA causes in vivo formation of lethal large gas emboli . As mentioned above, this is likely because i.v.…”
Section: Lipid‐based Microbubblesmentioning
confidence: 99%
“…Despite the increased mechanical advantages over LOMs, i.v. injection of higher doses of PHMs lead to increased incidences of pulmonary obstruction and death in a dose‐dependent manner . While not useful for CA, PLGA‐based PHMs would likely be ideal carriers for local or targeted oxygen (or other medical gas) delivery.…”
Section: Oxygen‐filled Hard‐shelled Polymeric Microbubblesmentioning
confidence: 99%
See 3 more Smart Citations